Flash back of the year 2011

I f 1 2011 + 201 1 2 1 = m n , If \frac{1}{\sqrt{2011+\sqrt{2011^{2}-1}}} =\sqrt{m} - \sqrt{n} , where m and n are positive integers , what is the value of m + n proof is needed compulsary. according to me the poster's of solution are the solvers


The answer is 2011.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Jan 21, 2015

It is given that:

1 2011 + 201 1 2 1 = m n \quad \quad \quad \dfrac {1}{\sqrt{2011+\sqrt{2011^2-1}}} = \sqrt{m}-\sqrt{n}

( 1 2011 + 201 1 2 1 ) 2 = ( m n ) 2 \quad \quad \quad \left( \dfrac {1}{\sqrt{2011+\sqrt{2011^2-1}}} \right)^2 = \left( \sqrt{m}-\sqrt{n} \right)^2

1 2011 + 201 1 2 1 = m + n 2 m n \quad \quad \quad \dfrac {1}{2011+\sqrt{2011^2-1}} = m + n - 2\sqrt{mn}

2011 201 1 2 1 ( 2011 + 201 1 2 1 ) ( 2011 201 1 2 1 ) = m + n 2 m n \quad \quad \quad \dfrac {2011-\sqrt{2011^2-1}}{(2011+\sqrt{2011^2-1})(2011-\sqrt{2011^2-1})} = m + n - 2\sqrt{mn}

2011 201 1 2 1 201 1 2 201 1 2 + 1 = m + n 2 m n \quad \quad \quad \dfrac {2011-\sqrt{2011^2-1}}{2011^2- 2011^2+1} = m + n - 2\sqrt{mn}

2011 201 1 2 1 = m + n 2 m n \quad \quad \Rightarrow 2011-\sqrt{2011^2-1} = m + n - 2\sqrt{mn}

m + n = 2011 4 m n = 201 1 2 1 \quad \quad \Rightarrow m + n = \boxed{2011} \quad \Rightarrow 4mn = 2011^2 - 1

absolutely right you are the real solver my friend

sudoku subbu - 6 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...